Pembuatan Biodiesel dari Virgin Red Palm Oil (VRPO) melalui Proses Transesterifikasi dan Penambahan Zat Aditif Minyak Sereh Wangi untuk Meningkatkan Cetane Number - Siti Iffat Tabriza; Harunsyah Harunsyah; Fachraniah Fachraniah (Politeknik Negeri Lhokseumawe, 2026)
This study aims to analyze the effect of reaction temperature and the addition of citronella oil as an additive on the characteristics of biodiesel produced from Virgin Red Palm Oil (VRPO) through a transesterification process. The reaction temperatures were varied at 50°C, 55°C, 60°C, and 65°C, while the volume of citronella oil ranged from 0 to 10 mL. The evaluated parameters included yield, viscosity, density, flash point, and cetane number. The results showed that increasing the temperature up to 60°C improved the biodiesel yield to 57%, while no significant increase was observed at 65°C due to methanol evaporation. The addition of citronella oil at 2–4 mL effectively increased the cetane number up to approximately 55.9 and improved the physical properties of biodiesel, particularly viscosity and flash point. However, excessive additive concentration (≥6 mL) led to a decline in biodiesel quality due to increased viscosity and reduced mixture homogeneity. GC-MS analysis indicated that the biodiesel was dominated by fatty acid methyl esters such as methyl oleate and methyl palmitate, which contribute to combustion performance and oxidative stability. The optimum condition was achieved at 60°C with the addition of 4 mL citronella oil, producing biodiesel with the best characteristics and potential to meet fuel quality standards.